Physical, Mechanical, and Durability Properties of OSB Prepared from CCB Treated Fast Growing Tree Species Strands - Wahyu Hidayat; Anne Carolina; Fauzi Febrianto (Jurnal Ilmu dan Teknologi Kayu Tropis, 2013)
The objective of this research was to evaluate the effect of preservative treatment of strands on the properties of oriented strand board (OSB) made from Paraserianthes falcataria, Maesopsis eminii and Acacia mangium strands. Prior to OSB manufacturing, strands were treated with chromium copper boron (CCB) soaking with concentration of 2% for 6 h. Three (3) layers OSB bonded with 7% of methylene diphenyl isocyanate (MDI) resin were produced with the core layer orientation perpendicular to the face and back layers. The results indicated that soaking strand with CCB significantly decreased the water absorption (WA) and thickness swelling (TS) values of OSB after immersed in water for 24 hours. Preservative treatment significantly decreased the mechanical properties of OSB (modulus of rupture/MOR parallel, modulus of elasticity/MOE parallel and internal bond/IB). Almost all board met the requirement of CSA 0437.0 standard for grade O-1 OSB panels, except board made from P. falcataria treated with preservative which did not achieve the requirement of TS, MOE in parallel direction, and IB. Preservative treatment strongly affected the durability of OSB. Soaking strand with CCB increased the resistance of OSB against termites attack 13.0 times higher than control board.Key words: chromium copper boron, fast growing tree species, methylene diphenyl isocyanate, oriented strand board